Availability of essential medicines during the COVID-19 pandemic: A qualitative study examining experiences and level of preparedness in Kenya. - Joseph Odhiambo Onyango; Dosila Ogira; Gilbert Kokwaro (Public Library of Science (PLoS), 2024)
This study examines the impact of the COVID-19 pandemic on the availability of essential medicines in Kenya and suggests actionable measures to enhance the country's preparedness for future pandemics. Utilising a cross-sectional qualitative design, the research combines a systematic review of the literature and 20 key informant interviews to provide a comprehensive analysis. The initial response to the pandemic involved resource reallocation, disrupting the procurement of essential medicines at national and county levels. Inefficiencies in these systems resulted in shortages and wastages of crucial medicines, exposing vulnerabilities in the health system. Furthermore, the study reveals regulatory policy weaknesses in Kenya, such as an inadequate legal framework for domestic pharmaceutical manufacturing and conflicting policies hindering medicine availability. The study recommends a multifaceted policy approach to ensure essential medicine availability during crises. Key recommendations include strengthening financial systems through increased government investments and innovative funding mechanisms, implementing price regulation policies, and enhancing the resilience of supply chain and procurement systems. Collaboration among various supply systems is essential to prevent stock-outs. Strengthening legislation and regulatory policies, increasing domestic pharmaceutical manufacturing capacity, and investing in health information systems are vital for sustained self-sufficiency and efficient service delivery. These comprehensive measures are essential to promote essential medicine availability, safeguard public health, and enhance resilience during crises.